Determinación de la calidad del agua utilizada en cultivos hortícolas en tres comunidades ubicadas en el distrito de San Juan Bautista Perú 2023 - Vásquez Soto, Victor Segundo (2025)
The study was carried out during the months of January to April 2023 in three communities in the district of San Juan Bautista, using in situ sampling methods and interview with the horticurists, with the objective of knowing the quality and quantity of irrigation water used by horticulturists in the district from the subsoil, for this It was necessary to carry out some measurements in the field (pH, TDS, electrical conductivity and temperature) and others in the laboratory (bioaccumulative heavy metals: lead and mercury), using standardized methodsfor bothin situ andlaboratory analysis. The main results indicate that the water used has excellent quality since it does not contain any bioaccumulative heavy metals and the volumes do not cause negative effects on the groundwater table because most of the water returns to the subsoil through percolation.